Bisphenol A Initiates Excessive Premature Activation of Primordial Follicles in Mouse Ovaries via the PTEN Signaling Pathway. (April 2018) - Hu, Ying; Yuan, Dong-zhi; Wu, Yi; Yu, Lin-lin; Xu, Liang-zhi; Yue, Li-min; Liu, Lin; Xu, Wen-ming; Qiao, Xiao-yong; Zeng, Ru-jun; Yang, Zhi-lan; Yin, Wei-yao; et al.
The essence of primary ovarian insufficiency (POI) is the premature exhaustion of primordial follicles in the follicle pool, which is caused by the excessive premature activation of primordial follicles after birth. Bisphenol A (BPA) exposure promotes the transition of primordial follicles to primary follicles, thus the number of primordial follicles in the primordial follicle pool decreases significantly. However, the molecular mechanisms underlying abnormal follicle activation are poorly understood. Phosphatase and tensin homologue (PTEN) signal system is a negative regulator of follicle activation, which is called the brake of follicle activation. Besides, BPA induces Michigan Cancer Foundation-7 breast cancer cells proliferation by dysregulating PTEN/serine/threonine kinase/p53 axis. Whether BPA initiates the excessive premature activation of primordial follicles in the mouse ovaries via PTEN signaling pathway is unclear. In this study, we treated 6-week-old female CD-1 mice with different concentrations of BPA to study the effect of BPA on follicular activation and development in vivo, as well as the role of PTEN signaling in this process. We observed that BPA in concentrations from 1 μg/kg to 10 mg/kg groups downregulated PTEN expression and initiated excessive premature activation of primordial follicles in the mouse ovaries, and this effect was partly reversible by PTEN overexpression. Our results improve the understanding of both the effect of BPA in occurrence of POI and molecular mechanisms underlying initiation of primordial follicle pool activation, thus providing insight for POI treatment and theoretical basis for reducing the risk of POI.